2021
DOI: 10.3389/fendo.2021.642131
|View full text |Cite
|
Sign up to set email alerts
|

Complications and Comorbidities of Acromegaly—Retrospective Study in Polish Center

Abstract: IntroductionIn acromegaly, chronic exposure to impaired GH and IGF-I levels leads to the development of typical acromegaly symptoms, and multiple systemic complications as cardiovascular, metabolic, respiratory, endocrine, and bone disorders. Acromegaly comorbidities contribute to decreased life quality and premature mortality. The aim of our study was to assess the frequency of acromegaly complications and to evaluate diagnostic methods performed toward recognition of them.Materials and MethodsIt was a retros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 48 publications
3
18
0
3
Order By: Relevance
“…The severity of these complications is correlated with diagnostic delay and the presence of active acromegaly (1). These include cardiovascular and metabolic complications (5,(12)(13)(14)(15), in addition to respiratory, intestinal, and skeletal disorders and particular neoplasms (5,14,(16)(17)(18)(19), all of which can impair patients' quality of life and may contribute to increased mortality (10). Women of reproductive age may also experience menstrual cycle disorders that coincide with the initial onset of acromegaly symptoms (20).…”
Section: Comorbiditiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The severity of these complications is correlated with diagnostic delay and the presence of active acromegaly (1). These include cardiovascular and metabolic complications (5,(12)(13)(14)(15), in addition to respiratory, intestinal, and skeletal disorders and particular neoplasms (5,14,(16)(17)(18)(19), all of which can impair patients' quality of life and may contribute to increased mortality (10). Women of reproductive age may also experience menstrual cycle disorders that coincide with the initial onset of acromegaly symptoms (20).…”
Section: Comorbiditiesmentioning
confidence: 99%
“…Women of reproductive age may also experience menstrual cycle disorders that coincide with the initial onset of acromegaly symptoms ( 20 ). Data from Bulgaria and Poland showed that 95% of patients suffered from comorbidities, with other endocrine and metabolic diseases and cardiovascular disease being the most common ( 12 , 21 ), co-occurring in 50% of patients ( 12 ). Of note, while the overall mortality in patients with acromegaly has decreased, the biochemical control of disease activity with normalized GH and IGF-I does not always correlate with clinical well-being ( 10 ).…”
Section: Comorbiditiesmentioning
confidence: 99%
“…Повече от 50% от пациентите с акромегалия имат сърдечно-съдови, метаболитни и ендокринни заболявания и само 5% от пациентите не страдат от друго заболяване [3]. Различни фактори предопределят тежестта и развитието на съпътстващи заболявания: нива на IGF-1, растежен хормон, възраст на пациента, продължителността на заболяването, размер на туморната маса, генетична предиспозиция и др.…”
Section: въведениеunclassified
“…11,12 Diabetes mellitus (DM) is a common complication of acromegaly, with a prevalence ranging from 19 -56%. 3,13 The primary mechanism of DM in acromegaly is growth hormone (GH)-induced insulin resistance, 14 thus hyperosmolar hyperglycemic state (HHS) would be expected as in Type 2 DM complications, instead of DKA. 15…”
Section: Introductionmentioning
confidence: 99%
“…Diabetic ketoacidosis (DKA) is both a potentially deadly hyperglycemic crisis and one of the most common causes of diabetes-related hospitalization in the U.S. 1 , 2 DKA currently is not established as a complication of acromegaly, 3 5 even though many authors have described their association. 6 , 7 This case reports a middle-aged male patient with a long history of untreated acromegaly who developed DKA.…”
Section: Introductionmentioning
confidence: 99%